Pengaruh Kepemimpinan, Budaya Kerja, dan Disiplin Kerja Terhadap Kinerja Pegawai di Kantor PDAM Tirta Moedal Semarang - Muhammad Abdillah; Sutarno Sutarno (Indo Publishing, 2026)
Human resources are a crucial instrument in achieving organizational goals and ensuring business sustainability. This study aims to analyze the influence of leadership, work culture, and work discipline on employee performance at PDAM Tirta Moedal Semarang. This research employs a quantitative approach, utilizing both primary and secondary data processed with the assistance of SPSS 25.0 software. The research population consists of all employees of PDAM Tirta Moedal Semarang, with a sample of 70 respondents selected using a saturated sampling technique. Data were collected comprehensively through questionnaires, observations, and literature review, and subsequently analyzed using multiple linear regression, t-tests, F-tests, and coefficient of determination analysis. The results of the multiple linear regression analysis produced the following equation model Y=8.795+1.398X1​−0.054X2​+0.034X3​+e. Based on partial testing (t-test), it was found that only the leadership variable has a significant effect on employee performance, while work culture and work discipline do not have a significant effect. However, the F-test results show an F-value of 23.850 with a significance level of 0.000 (p < 0.05), indicating that the model is appropriate and reliable for predicting the simultaneous influence of leadership, work culture, and work discipline on employee performance. Furthermore, the coefficient of determination (adjusted ????2) of 0.498 indicates that these three independent variables explain 49.8% of the variance in employee performance, while the remaining 50.2% is explained by other variables outside the scope of this study.